Efficacy of injectable platelet-rich fibrin (i-PRF) as a novel vehicle for local drug delivery in non-surgical periodontal pocket therapy: A randomized controlled clinical trial - Murugan Thamaraiselvan; Nadathur Doraisamy Jayakumar (Journal of Advanced Periodontology and Implant Dentistry)
Background. The vehicle in a local drug delivery (LDD) system plays a vital role in delivering the active drug component at the diseased site. Liquid/injectable platelet-rich fibrin (i-PRF), an autologous fibrin matrix, might be used as a vehicle to enmesh drugs and deliver locally at the periodontally diseased sites. This study evaluated the efficacy of the drug (ciprofloxacin [Cip])-loaded i-PRF as a LDD system adjunct to subgingival debridement in subjects with periodontal pockets. Methods. In a parallel design study, 79 periodontally diseased pocket sites were randomized to 3 groups: group 1 (n=25), scaling and root planing (SRP)+i-PRF+Cip; group 2 (n=25), SRP+i-PRF; group 3 (n=25), SRP without any adjunctive intervention. Clinical parameters (probing depth [PD], clinical attachment level [CAL], gingival index [GI], plaque index [PI]) and microbial quantification (relative quantification of levels of Aggregatibacter actinomycetemcomitans) were assessed from baseline to 6th and 12th weeks of follow-up. Results. All the treatment groups showed significant improvements in the clinical and microbial parameters assessed. Group 1 showed significantly higher PD and GI reduction with CAL gain and decreased in relative levels of A. actinomycetemcomitans in the 12th week, followed by group 2 compared to group 3. Conclusion. Thus, within the limits of this study, it can be concluded that i-PRF could be considered a potential LDD vehicle for the delivery of ciprofloxacin in periodontal pocket therapy.